The Existence of Semilir Beach Tourism on The Feasibility of Small Traders' Income in Socorejo Village, Jenu District, Tuban Regency - Yusuf, Muhammad; Munir, Miftachul (Universitas Muhammadiyah Gresik, 2025)
The tourism sector in Indonesia is an inseparable part of national development. The development of tourism in an area will bring many benefits to the community, namely economically, socially and culturally. The purpose of this study was to find out how much tourist attractions contribute to providing a place for small traders (kiosks) on Semilir Beach, Socorejo Village and the income generated by small traders whether it is above the UMK or below the UMK. The data analysis method used by the researcher is Miles and Huberman's qualitative data analysis. In the implementation of field research, primary data is a source of data obtained directly from the original, namely data from observations, questionnaires, interviews and those obtained directly from the observation site. The research was carried out by researchers on May 21, 2024. Semilir Beach tourism provides benefits and also contributes to the people of Socorejo Village/provides opportunities to trade/make kiosks. The income that has been obtained from traders is IDR. 38,400,000,- for 1 year and if calculated per month is income for 1 year/12 months equal to RP. 38,400,000,- / 12 which is RP. 3,200,000,- then reduced by rental fee of RP. 125,000,- per month. Equal to RP. 3,075,000,- while UMK of Tuban Regency is RP. 2,739,224.88. From the calculation above, it can be interpreted that the income of traders in Semilir Beach tourism in Socorejo is above UMK, income is often above UMK sometimes also more during holidays or big days and national holidays.